Muito além da valsa Gotas de Lágrimas: o violão seresteiro de Mozart Bicalho em transcrições e arranjos de seus álbuns Sonhando ao Luar e um Senhor Violão - Reginaldo de Almeida Martins (2013)
This work intends to cooperate with the preservation of composer and guitarist Mozart Bicalho's life registries and works. The aim of this research was not only to contextualize the composers production in Brazilian musical scenario, but also to amplify the repercussion of his works through the transcription of thirteen pieces from the albums Sonhando ao Luar and Um Senhor Violão, de 1968. Here, three transcriptions were used as the basis for the creation of solo guitar arrangements.